(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective: Whom sports for health aims to ensure a healthy and safe event for women. The study aims to determine college women students' physiological responses to hydraulic resistance training. Although this hydraulic resistance training effect can reflect the resting pulse rate, systolic pressure and diastolic pressure, resistance exercise may be safer for all populations, especially for untrained women. Methods: They were randomly divided and assigned into two groups of fifteen each as the experimental group (HRTG) 1(n=15) and control group 1 (n=15). The data were collected before and after the training of 8 weeks, paired sample t-test was used to find the significant difference between the groups. Results: The Statistical analysis of the HRTG, the control group of paired sample t-test. The obtained t-test of significant improvement in resting pulse rate is 41.01, systolic pressure is 40.44, and diastolic pressure is 31.59 of post-test was more significant than the table value of the degree of freedom 2.76 (14) required for the significance at 0.05 level. The hydraulic resistance training group responded to the training with a more positive influence on physiological variables, when compared hydraulic resistance training group better than the CG. Conclusion: It concluded that the study significantly improved the hydraulic resistance training and improved their resting pulse rate, systolic pressure and diastolic pressure and enhanced their daily activity level of fitness and improved lifestyle.